Pengelolaan Dana ZIS Upaya Memperdayakan Ekonomi Masyarakat Dhuafa Pada LAZIS Sabilillah Malang - Purnamasari, Puji Endah; Shahab, Zahra Aulia (Jurnal Manajemen, 2022)
A B S T R A C T Zakat in the study of fiqh is the cleansing of property owned by a person. This aims to share rizki with others because in every property owned by a person there are other people's rights that must be issued. With the existence of zakat is expected to be able to even out the welfare of the surrounding community. Good and right management of zakat funds is an effort to improve the benefit of the surrounding community. Therefore, zakat, infaq and shodaqoh (ZIS) are usually managed by an official and legal entity that is trusted by the community to manage the ZIS funds properly. Usually these funds are managed through certain programs so that they are expected to be able to distribute the zakat funds evenly and on target. One of the ZIS institutions in Malang is LAZIS Sabilillah, which has long developed and is trusted by the community to channel ZIS funds which are sought as a welfare program for the poor.This research uses a descriptive qualitative approach. The object of this research is LAZIS Sabilillah Malang. Data collection includes observation, interviews and documentation. The analysis used in this research is collecting data, presenting data and finding conclusion. The results of this study indicate that LAZIS Sabilillah manages ZIS funds by implementing several empowerment programs, namely the Guidance Program, Sabilillah Entrepreneur Education (SEI), Mustahik Welfare (Bina Usaha), Routine Incentives for Koran Teachers and Takmir Musolla fostered and compensation for 8 existing donations (Fakir , Poor, Ghorim, Musafir, Mualaf) to develop productive zakat funds for poor people. LAZIS Sabilillah carries out supervision of mustahik in two ways, both from an economic perspective and for worship as a basis for evaluation. In addition, LAZIS Sabilillah also strives to improve Mustahik's economy by providing business coaching and providing venture capital.